“The Noble Savage and the Civilised Brute: Nature and the Subaltern Angst in Swarup Dutta’s Machh Master (The Expert Angler) - Sajalkumar Bhattacharya (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2009)
Parallel reading of history from the subaltern point of view is not only possible, but it also often proves to be revealing. It often unearths a new discourse, which challenges the canonized history or even subverts it. This paper offers a reading of a recent Bhasa (Bangla) novel Machh Master (The Expert Angler) where the Naxalite Movement that rocked Bengal in the sixties, has been narrated and analysed from the viewpoint of one dalit subaltern. The novel attempts to create a binary between this ‘uncorrupted’ world/mode of existence and the civilized, sophisticated, intellectual, but essentially ‘corrupted’ urban world. In this natural savage world and its eco-system, the urban, elitist Naxalite movement turns out to be nothing but an imposition and an intrusion. At the end, disillusioned Neul detaches himself from this movement, goes back to, and embraces Nature in a desperate bid to get back his pre-lapserian mode of existence. Neel, chief agent of the Naxalite movement, too is influenced by these children of Mother Nature, and undergoes a transformation. This paper explores this interesting role of Nature in this new reading of the history of mankind.